2017
DOI: 10.1109/tse.2016.2630689
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of App Store Analysis for Software Engineering

Abstract: App Store Analysis studies information about applications obtained from app stores. App stores provide a wealth of information derived from users that would not exist had the applications been distributed via previous software deployment methods. App Store Analysis combines this non-technical information with technical information to learn trends and behaviours within these forms of software repositories. Findings from App Store Analysis have a direct and actionable impact on the software teams that develop so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
250
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(258 citation statements)
references
References 211 publications
(186 reference statements)
1
250
0
7
Order By: Relevance
“…Among the most studied platforms for obtaining user feedback are app stores. Martin et al [11] survey the most relevant work in the area. We focus on literature performing the same steps as our approach: classification, grouping and ranking.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the most studied platforms for obtaining user feedback are app stores. Martin et al [11] survey the most relevant work in the area. We focus on literature performing the same steps as our approach: classification, grouping and ranking.…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, we compare against three additional weighting schemes: W survey m W survey m W survey m , which uses the W survey weighting scheme but has manually assigned labels for the category attribute-instead of the ones automatically predicted by the classifier, used by the rest of the weighting schemes in this experiment, W no social W no social W no social where all social attributes (i.e., retweets, likes and social rank) are eliminated and emphasis is given on the following attributes: category (w 1 =0.50), duplicates (w 6 =0.33) and sentiment (w 4 =0.16), while w 2 = w 3 = w 5 = 0 and W no mentions W no mentions W no mentions which also uses the W survey scheme but which only ranks tweets that are not mentions 11 . We ran the implementation of the ranking function with the four weight variations on all of the tweets in our truthset.…”
Section: Rankingmentioning
confidence: 99%
“…For example, Gorla et al [6] used API calls to understand how anomalous API calls can highlight aberrant or otherwise suspicious behaviour, while Syer et al [25] used API calls to understand the relationship between defects and platform dependence. A comprehensive survey of App Store Analysis for Software Engineering can be found in the authors' recent survey [22].…”
Section: App Store Analysismentioning
confidence: 99%
“…Martin et al [24] conduct a survey in app store analysis in which they describe and compare studies that focus on analyzing star ratings and user reviews. Harman et al mined 32,108 BlackBerry apps and found a strong correlation between the average star rating of an app and the number of downloads [11].…”
Section: Analyzing Star Ratings and Reviews Of Appsmentioning
confidence: 99%